Los ejércitos en tiempos de tregua durante las guerras de independencia de Venezuela: entre conscripciones y felonías (2021)
Within the framework of the Bicentennial of the Independence of the Latin American nations, this article analyzes the complicated challenge of the conservation of the troops in Venezuela during the phase of the ceasefire decreed by the armistice signed in 1820 in Trujillo. In this internal dynamic of the military forces, the strong influence of the prevailing political environment and the fluctuating game of loyalties in this final phase of the independence process could be verified. Within the stream of new military history, an attempt is made to examine not only recruitment efforts but also high levels of desertion and changing sides that were especially detrimental to the royalist side, which ultimately ended up tipping the balance towards the realist side. Republican side. Finally, the process of replenishing the force is addressed, either through pardon for new recruits.